Joel Barlow : American citizen in a revolutionary world - Buel, Richard, 1933- (Johns Hopkins University Press, 2011)
"Poet, republican, diplomat, and entrepreneur, Joel Barlow filled many roles and registered impressive accomplishments. In the first biography of this fascinating figure in decades, Richard Buel Jr. recounts the life of a man more intimately connected to the Age of Revolution than perhaps any other American. Barlow was a citizen of the revolutionary world, and his adventures throughout the United States and Europe during both the American and French Revolutions are numerous and notorious. From writing his epic poem, The Vision of Columbus, to plotting a republican revolution in Britain to negotiating the release of American sailors taken captive by Barbary pirates, Joel Barlow personified the true spirit of the tumultuous times in which he lived. No one witnessed more climactic events or interacted with more significant people than Joel Barlow. It was his unique vision, his unfailing belief in republicanism, and his entrepreneurial spirit that drove Barlow to pursue the revolutionary ideal in a way more emblematic of the age than the lives of many of its prominent heroes. Buel is a knowledgeable guide, and in telling Barlow's story he explores the cultural landscape of the early American republic and engages the broader themes of the Age of Revolution. Few books explore in such a comprehensive fashion the political, economic, ideological, diplomatic, and technological dimensions of this defining moment in world history."--Front flap